Impact of different adjuvant treatment strategies on survival in stage III endometrial cancer: a population-based study. (1st November 2019) - van Weelden, WJ; Reijnen, C; Eggink, F; de Lange, N; Nijman, H; Boll, D; van der Aa, M; Pijnenborg, J
Abstract : Introduction/Background: Endometrial cancer (EC) is the most common gynecological cancer in the Western world. For those with advanced stage EC outcome is significantly worse despite adjuvant treatment. Different adjuvant treatment strategies for these patients have been compared in the GOG-258 and PORTEC-3 studies. Since EC patients are mainly elderly women with substantial comorbidity, these patients are often underrepresented in clinical trials. The aim of this study is to evaluate outcome in stage III EC patients, according different applied treatment strategies in a population based study. Methodology: All patients treated for FIGO stage III EC in the period 2005–2015 were extracted from the Netherlands Cancer Registry (NCR). Patients without surgery, and those with residual tumor after surgery were excluded from analyses. The 5-year overall survival was compared for different adjuvant treatment strategies: observation, vaginal brachytherapy (VBT), external beam radiation (EBRT), chemotherapy (CT), and chemoradiation (CRT). Results: A total of 997 EC patients were eligible for analysis. The mean age at diagnosis was 67, and most patients (68%) were diagnosed with endometrioid histology. Adjuvant treatment was applied in 83%, and consisted of EBRT/VBT (53%), CT (12%), and CRT (15%). Patients >70 years more often received no adjuvant treatment, 23% compared to 13% (<70). Chemoradiation was more frequent applied for serous (24%) and carcinosarcoma (28%), compared to endometrioid (11%) and clear cell (9%) EC. The 5-year overall survival was significantly better in patients that CRT compared to EBRT, 66% (53–76%) and 58% (49–61%) respectively. This survival benefit for patients treated with adjuvant CRT remained significant in multivariable Cox regression analysis (HR 0.68, 0.49–0.94 95% CI). Conclusion: This population based study demonstrates the benefit of chemoradiation in FIGO III EC, with a significant better 5-year overall survival compared to external beam radiation. Disclosure: Nothing to disclose.